Teaching and Learning English Using Differentiated Learning Strategy in Merdeka Curriculum at Remote Island : Calssroom Practices - Wahdaniah Wahdaniah; Sultan Baa; Chairil Anwar Korompot; Muhammad Tahir (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to examine the teaching and learning process through the implementation of differentiated learning strategy for teaching speaking in the Merdeka Curriculum at a remote island school. Employing a case study design, data were collected through direct classroom observation. Participants were selected using purposive sampling, involving one English teacher and five eighth-grade students. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the teacher applied differentiation based on students’ readiness, interests, and learning profiles by using varied speaking tasks, contextual materials, and flexible grouping. Despite constraints such as limited technology, restricted instructional time, and lack of resources, the differentiated learning strategy fostered student engagement and improved speaking confidence. The results indicate that differentiated learning, when implemented responsively, can enhance inclusive and effective speaking instruction in remote educational settings.